Diagnostic challenge of Strongyloides stercoralis hyperinfection syndrome - Šterbenc, Anja (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2022)
Strongyloides stercoralis causes chronic, mostly asymptomatic infections but hyperinfection syndrome may occur in immunosup- pressed patients, especially in those receiving corticosteroids. We report a case of S. stercoralis hyperinfection syndrome in a solid organ transplant recipient that occurred approximately 2.5 months after heart transplantation. The patient presented to the inten- sive care unit with acute respiratory distress, bacteremia, and petechial rash on abdomen and toe. Microbiology testing of respira- tory samples excluded infection with Pneumocystis jirovecii, respiratory viruses, pathogenic bacteria and fungi. No eosinophilia was found. Histopathological examination of the skin biopsy of the petechial rash provided the first indication of the diagnosis, revealing the presence of isolated filariform S. stercoralis larvae in the dermis. Subsequent microbiology testing confirmed the diagnosis. This case highlights the role of histopathological examination of a skin rash in diagnosing patients with atypical clinical presentation of Strongyloides hyperinfection syndrome.
Keywords: hyperinfection syndrome; sindrom hiperinfekcije; Strongyloides stercoralis; transplant; transplantacija